Understanding postgraduate students’ perceptions of plagiarism: a case study of Vietnamese and local students in New Zealand - Minh Ngoc Tran; Linda Hogg; Stephen Marshall (International Journal for Educational Integrity, 2022)
Abstract Despite increasing scholarly interest in tertiary student perceptions of plagiarism, very little is known about those held by postgraduate (PG) students, although differences between undergraduate (UG) and PG students relate to both their characteristics and the demands of their studies. Furthermore, there is a dearth of research within the context of international education, where managing plagiarism is seen as a major challenge. This paper reports on a recent online survey with 207 Vietnamese (n = 72) and local (n = 135) PG students at a New Zealand university regarding their perceptions of plagiarism. The findings showed significant differences both between and within the two groups. Perception variations arose from a range of influences and prior experiences, not just the culture in which the students were initially educated. Differences related to participants’ age, gender, academic levels, disciplines, and teaching experience. This study’s findings contribute knowledge about under-researched PG students and problematize prevalent stereotypes of international students regarding plagiarism. They generate implications for higher education institutions to accommodate international and domestic PG student needs in ways that respect their diversities in detail as individuals, not as members of a homogeneous group. Further qualitative research to explore PG student perceptions in greater depth is recommended.